HARMONISASI KODE ETIK PROFESI GURU DENGAN UNDANG-UNDANG NOMOR 14 TAHUN 2005: SUATU KAJIAN YURIDIS NORMATIF - Salsabila, Elmira; Solehuddin, M. Sugeng; Rahmawati, Niken (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2026)
Teacher professionalism is determined not only by the mastery of competencies but also by adherence to legal norms and the professional code of ethics. The rise in cases involving teachers such as the "Ms. Salsa" case, allegations of excessive student searches in Jember, and the involvement of students in public speaking/rally activities in East Tanjung Jabung highlights the importance of harmonizing the Indonesian Teacher Code of Ethics with Law Number 14 of 2005 concerning Teachers and Lecturers. This study aims to analyze the alignment between these two instruments and identify challenges regarding their implementation in the teaching profession in Indonesia. The research employs a normative legal method (doctrinal legal research) utilizing statutory, conceptual, and case-based approaches. Data were gathered through a literature review of legislation, professional codes of ethics, scholarly works, and relevant actual cases, followed by qualitative analysis using grammatical, systematic, and teleological interpretation. The findings indicate that, from a normative standpoint, the Indonesian Teacher Code of Ethics aligns with Law Number 14 of 2005 in affirming professionalism, integrity, student protection, and the moral responsibilities of teachers. However, certain aspects require strengthening, including the lack of uniform enforcement mechanisms for the code of ethics, suboptimal regulation of teacher ethics in the digital space, and weak coordination among law enforcement, employment disciplinary measures, and code of ethics enforcement. Therefore, it is necessary to update the code of ethics to adapt to technological advancements, strengthen integrated enforcement mechanisms, and foster professional ethics continuously to enhance teacher professionalism, legal certainty, and public trust in the education system. Keyword: Legal Harmonization, Teacher Code Of Ethics, Teacher Professionalism, Professional Ethics.